Non-traditional security in contemporary Chinese international relations thought - Stieber, Sabine (2017)
‘Security’ has been undergoing a process of re-conceptualisation since the Cold War. Realism’s dominance meant that security concerned the survival of the nation-state in the face of military aggression. This clear-cut ‘traditional security’ has been contested since the 1970s, when ‘non-traditional security’ (NTS) covering non-military threats began to be discussed. Security Studies now encompasses varying approaches and interpretations. The concept of security is evolving substantially, but the debate is mostly limited to Western voices. Yet NTS has sparked a lively discourse in the PRC. The thesis establishes Chinese International Relations (IR) scholars’ understanding of NTS, based on the close textual analysis of academic publications and on interviews conducted with authors and other IR-specialists in China. It enquires into what these scholars mean when discussing NTS, and whether their conceptions differ from the mainstream, mainly Western, IR discourse. It then investigates the ten issues generally deemed NTS in the Chinese debate: culture and information security; terrorism and transnational crime; economic security and migration; energy and environmental security; and health and food security, analysing their conceptualisations, assigned importance, causes for variance within the debate, emerging political meanings and implications, and possible normative implications. The study shows that the scholarly NTS debate in China is diverse, ranging from a more statist expansion of national security to non-military threats to a theoretically deeper discourse which embraces individual security. Although the debate encompasses political purposes of vindicating state securitisation and advocating state management, some scholars’ arguments have normative implications of moving towards a people-centric view of security encouraging a change in global politics. The debate in China is still in flux, without universally accepted definitions, but a normative turn is evident which means that Chinese IR theory overall moves beyond descriptive theory. The study contributes to the wider research by adding to our understanding of how China ‘sees’ the world, and to the debate on NTS by critically examining the Chinese thought vis-à-vis the mainstream literature.